The nexus between carbon emissions, energy consumption and economic growth in Middle East countries: A panel data analysis - Ozcan, Burcu (Elsevier Sci Ltd, 2013)
The environmental Kuznets curve (EKC) hypothesis assumes that there is an inverted U-shaped relationship between environmental degradation and income per capita. In other words, as a country grows, it is assumed that its environmental quality improves. In this study, we aim to test the EKC hypothesis for 12 Middle East countries during the period 1990-2008 by employing recently developed panel data methods. Our results provide evidence contrary to the EKC hypothesis. We found evidence favorable to the U-shaped EKC for 5 Middle East countries, whereas an inverted U-shaped curve was identified for only 3 Middle East countries. Furthermore, there appear to be no causal links between income and CO2 emissions for the other 4 countries. Regarding the direction of causality, there appears to be a unidirectional causality from economic growth to energy consumption in the short-run; in the long-run, however, the unidirectional causality chain runs from energy consumption and economic growth to CO2 emissions. We also suggest some crucial policy implications depending on these results. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Environmental Kuznets curve; CO2 emissions; Panel cointegration